Is the QTM controversy settled? - Bhanumurthy, N.R.; Padhan, Purna Chandra; Ramachandran, M. (Bangalore, 2001)
The present study tests the validity of the Quantity Theory of Money with the help of a new test procedure developed by Horvath & Watson (Econometric Theory, 1995) in a multiple cointegration framework. By using a fairly long quarterly data set of USA, Canada, Australia and Italy for the period 1975-I to 1998-II the study found that I(0) velocity is proved in all the sample countries, except Canada. Further, it found that all the sample countries have at least one unknown cointegrating vector between money supply, prices and real income, corroborating the propositions of QTM.
Keywords: Money; Quantity Theory